Rebuilding communities and lives the role of damayan and bayanihan in disaster resiliency. - Barrameda, Teresita V. (Philippine Journal of Social Development, 2011)
The study explores the roles played by damayan (mutual aid) and bayanihan (cooperation and volunteerism) in the lives of people in five rural communities in Albay Province. It highlights how these indigenous practices serve as social resource in the people's day-to- day survival; as coping mechanisms in times of typhoons and flooding; and, as adaptive strategies in building their resiliency. The study shows that these practices help in developing their own sub-cultures of safety and promoting the emotional well-being of the people. There were limitations in these indigenous practices, requiring external support to sustain the people's initiatives for recovery. The study also provides insights and proposals on how local government units and organizations in the disaster field can utilize damayan and bayanihan in disaster risk reduction.